14-3-3γ mediates the long-term inhibition of peripheral kappa opioid receptor antinociceptive signaling by norbinaltorphimine. (1st December 2022) - Wedemeyer, Michael J.; Jennings, Elaine M.; Smith, Hudson R.; Chavera, Teresa S.; Jamshidi, Raehannah J.; Berg, Kelly A.; Clarke, William P.
Abstract: Long-term inhibition of kappa opioid receptor (KOR) signaling in peripheral pain-sensing neurons is a potential obstacle for development of peripherally-restricted KOR agonists that produce analgesia. Such a long-term inhibitory mechanism is invoked from activation of c-Jun N-terminal kinase (JNK) that follows a single injection of the KOR antagonist norbinaltorphimine (norBNI). This effect requires protein synthesis of an unknown mediator in peripheral pain-sensing neurons. Using 2D difference gel electrophoresis with tandem mass spectrometry, we have identified that the scaffolding protein 14-3-3γ is upregulated in peripheral sensory neurons following activation of JNK with norBNI. Knockdown of 14-3-3γ by siRNA eliminates the long-term reduction in KOR-mediated cAMP signaling by norBNI in peripheral sensory neurons in culture. Similarly, knockdown of 14-3-3γ in the rat hind paw abolished the norBNI-mediated long-term reduction in peripheral KOR-mediated antinociception. Further, overexpression of 14-3-3γ in KOR expressing CHO cells prevented KOR-mediated inhibition of cAMP signaling. These long-term effects are selective for KOR as heterologous regulation of other receptor systems was not observed. These data suggest that 14-3-3γ is both necessary and sufficient for the long-term inhibition of KOR by norBNI in peripheral sensory neurons. Graphical abstract: Image 1 Highlights: 14-3-3γ expression increased after JNK activation with norBNI in sensory neurons. 14-3-3γ is required for long-term inhibition of KOR cAMP signaling. 14-3-3γ is required for long-term inhibition of KOR-mediated antinociception. Overexpression of 14-3-3γ in CHO cells eliminates KOR-mediated cAMP signaling.